Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1177/0269215517718892
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of a combined self-management and exercise intervention for elderly people with osteoarthritis of the knee: the PLE2NO program

Abstract: This study supports the importance of a combined self-management and exercise intervention to improve functional lower limb strength and aerobic capacity in a Portuguese sample. Additionally, pain and other symptoms have improved clinically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 38 publications
2
56
0
6
Order By: Relevance
“…However, one data set was duplicated and published in two different manuscripts38 39; therefore, the later one was excluded 38. From the 23 studies included in this SR, most studies (n=19) evaluated QoL,39–57 one study evaluated self-efficacy,56 one study evaluated helplessness,58 one evaluated pain catastrophising,56 two evaluated coping strategies,56 59 one evaluated depression and psychological distress,60 and one evaluated cognitive symptom management (CSM)61 in individuals with knee OA. The study of Broderick et al 56 considered more than one outcome as primary.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, one data set was duplicated and published in two different manuscripts38 39; therefore, the later one was excluded 38. From the 23 studies included in this SR, most studies (n=19) evaluated QoL,39–57 one study evaluated self-efficacy,56 one study evaluated helplessness,58 one evaluated pain catastrophising,56 two evaluated coping strategies,56 59 one evaluated depression and psychological distress,60 and one evaluated cognitive symptom management (CSM)61 in individuals with knee OA. The study of Broderick et al 56 considered more than one outcome as primary.…”
Section: Resultsmentioning
confidence: 99%
“…There was very limited evidence from one study61 with small effect in favour of a combined self-management programme and exercise intervention to improve CSM of individuals with knee OA compared with self-management programme only (SMD=0.52, CI 0.03 to 1.01) (figure 6). …”
Section: Resultsmentioning
confidence: 99%
“…Also, when comparing Tai Chi or Yoga with aquatic and aerobic exercise [30,35], there were uncertain results on symptom improvement, pain relief, and perceived function. In five studies [44,45,[47][48][49], active exercise represented the only intervention group, and in all of those participants in the study group showed significant improvement in the checked outcomes, such as WOMAC, KOOS, VAS, 6-MWT, and get-up-and-go test. On the other hand, only one study [43] reported no differences between the rehabilitation group and the control group in any outcome measure.…”
Section: Discussionmentioning
confidence: 99%
“…Of the RCTs, six studies checked sports activity n = 4 Tai Chi [30][31][32][33], n = 2 yoga [34,35]. The remaining RCTs were focused on water-based and land-based exercises: there were three studies with three arms (hydrotherapy, land-based exercise and control group) [36][37][38], four studies that compared only hydrotherapy with controls [39][40][41][42], and seven studies that only evaluated land-based exercises [43][44][45][46][47][48][49].…”
Section: Included and Excluded Studiesmentioning
confidence: 99%
See 1 more Smart Citation